Long-term outcome after helical tomotherapy following breast conserving surgery for ductal carcinoma in situ - Hauswald, Henrik; Schempp, Michael; Liebig, Pauline; Hoefel, Sebastian; Debus, Jürgen; Huber, Peter E.; Zwicker, Felix (Technology in cancer research & treatment, 2024)
Background: This retrospective study aimed to investigate the outcomes and adverse events (AEs) associated with adjuvant radiotherapy with helical tomotherapy (hT) after breast-conserving surgery (BCS) for ductal carcinoma in situ (DCIS). Methods: Twenty-eight patients with DCIS underwent postoperative hT between 2011 and 2020. hT was chosen since it provided optimal target coverage and tolerable organ-at-risk doses to the lungs and heart when tangential 3-dimensional conformal radiotherapy (3D-CRT) was presumed to provide unfavorable dosimetry. The median total (single) dose was 50.4 Gy (1.8 Gy). The median time between BCS and the start of hT was 5 weeks (range, 4-38 weeks). Statistical analysis included local recurrence-free survival, overall survival (OS), and secondary cancer-free survival. AEs were classified according to the Common Toxicity Criteria for Adverse Events, version 5. Results: The patients’ median age was 58 years. The median follow-up period was 61 months (range, 3-123 months). The 1-, 3-, and 5-year OS rates were 100% each. None of the patients developed secondary cancer, local recurrence, or invasive breast cancer during follow-up. The most common acute AEs were dermatitis (n = 27), fatigue (n = 4), hyperpigmentation (n = 3), and thrombocytopenia (n = 4). The late AE primarily included surgical scars (n = 7) and hyperpigmentation (n = 5). None of the patients experienced acute or late AEs > grade 3. The mean conformity and homogeneity indices were 0.9 (range, 0.86-0.96) and 0.056 (range, 0.05-0.06), respectively. Conclusion: hT after BCS for DCIS is a feasible and safe form of adjuvant radiotherapy for patients in whom 3D-CRT is contraindicated due to unfavorable dosimetry. During follow-up, there were no recurrences, invasive breast cancer diagnoses, or secondary cancers, while the adverse effects were mild.